2006
DOI: 10.1016/j.ejcts.2006.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin in experimental and clinical heart failure

Abstract: Doxorubicin-induced heart failure is a rare but serious illness due to the well-known treatment difficulties. Prevention strategies have not demonstrated the expected success and unfortunately, this specific type of heart failure does not respond to the usual medical therapy as other kinds of heart failure. Therefore, surgical procedures may be necessary in some patients. Cardiac transplantation is performed in most cases but it requires the cure of the neoplastic disease. This usually requires a recurrence-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 61 publications
(104 reference statements)
0
43
0
Order By: Relevance
“…Caspase-3 activation is a key step in apoptosis. Accordingly, inhibition of doxorubicin-induced cardiomyocyte apoptosis by modulation of the factors that control apoptosis may provide new opportunities for the prevention and treatment of doxorubicin-induced cardiomyopathy (Christiansen and Autschbach, 2006;Narula et al, 1999;Takemura and Fujiwara, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-3 activation is a key step in apoptosis. Accordingly, inhibition of doxorubicin-induced cardiomyocyte apoptosis by modulation of the factors that control apoptosis may provide new opportunities for the prevention and treatment of doxorubicin-induced cardiomyopathy (Christiansen and Autschbach, 2006;Narula et al, 1999;Takemura and Fujiwara, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the development of doxorubicin cardiomyopathy involves apoptosis of cardiomyocytes (L'Ecuyer et al, 2006;Takemura and Fujiwara, 2007). Since cardiomyocyte apoptosis contributes to the development of myocardial dysfunction in heart failure, inhibition of doxorubicin-induced cardiomyocyte apoptosis may provide new opportunities for the prevention and treatment of doxorubicin-induced heart failure (Christiansen and Autschbach, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical use of this drug is limited because of cardiotoxicity, which might proceed to irreversible heart failure (Swain et al, 2003;Christiansen and Autschbach, 2006;Outomuro et al, 2007;Carvalho et al, 2009). Although several mechanisms have been proposed to describe the mechanisms by which DOX induces cardiotoxicity, these mechanisms are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…DOX is a potent chemotherapeutic agent that is used in the treatment of solid tumors and malignant hematological diseases (2). DOX exerts its antitumor activity by inserting into DNA, leading to double-stranded DNA breaks (DSB), and intercepting DNA topoisomerase II activity (3,4).…”
Section: Introductionmentioning
confidence: 99%